Elevation of immunoglobulin levels is associated with treatment failure in HIV-infected children in Vietnam - Dang LVP (Dove Medical Press, 2018)
Linh Vu Phuong Dang,1 Viet Hung Pham,2 Duc Minh Nguyen,3 Thanh Thi Dinh,1 Thu Hoai Nguyen,4 Thanh Hai Le,5 Van Lam Nguyen,6 Thi Phuong Vu7,8 1Public Health Laboratory, Hanoi University of Public Health, Hanoi, Vietnam; 2Department of Microbiology, Vietnam National Hospital of Pediatrics, Hanoi, Vietnam; 3Department of Geriatrics, National Hospital of Acupuncture, Hanoi, Vietnam; 4Department of Training and Direction Activity, National Geriatric Hospital, Hanoi, Vietnam; 5Department of Emergency, Vietnam National Hospital of Pediatrics, Hanoi, Vietnam; 6Department of Infectious Disease, Vietnam National Hospital of Pediatrics, Hanoi, Vietnam; 7Department of Biochemistry, Hanoi Medical University, Hanoi, Vietnam; 8Department of Biochemistry, Dinh Tien Hoang Institute of Medicine, Hanoi, Vietnam Background: HIV-infected children suffer from higher levels of treatment failure compared to adults. Immunoactivation, including humoral immunoactivation reflected by increased immunoglobulin levels, is believed to occur early during HIV infection. Therefore, we wanted investigate alteration in immunoglobulin levels in association with treatment response in HIV-infected children. Methods: A nested case–control study was conducted using clinical data collected from 68 HIV-infected children enrolled at the National Hospital of Pediatrics, Vietnam. Results: The results showed that immunoglobulin levels, CD4 T-cell counts, CD4 T-cell percentage, and HIV load were significantly higher in the treatment-failure group than the treatment-success group at treatment initiation. IgG and IgA levels were negatively correlated with CD4 T-cell counts (P=0.049 and P<0.01, respectively) and positively correlated with HIV load (P=0.04 and P=0.02, respectively). In addition, IgG and IgA levels were independently associated with treatment response, analyzed by Cox regression analysis (HR 1.19 [P=0.049] and HR 1.69 [P<0.01], respectively). Conclusion: Elevation of IgA levels occurred early during HIV infection, and might have a prognostic role in treatment response. Keywords: antiretroviral therapy, HIV1, immunoglobulin, IgG, IgA, treatment failure